Suitability of Managed Retreat for Honolulu - Hahn, Heidi; Jung, Mijeong; Bluestein, Harrison; Rodgers, Maddie (University of Virginia, 2023)
The goal of this project is to illuminate the question that if, under a projected 7-foot sea level rise, what land would theoretically be available and where would that distribution occur? This project utilizes a 7-foot sea level rise- a worst-case scenario in the Primary Urban Center of Honolulu, Hawaii as a means of illustrating the severity of the issue. Our group outlines several variables, including slope, FEMA flood zones, current zoning classifications, streams, and road infrastructure. Due to Hawaii’s remote location, the ability to access resources, rebuild infrastructure in an adequate timeframe becomes difficult, lending more credence for proactive adaptation.
Original submission date: 2023-07-30T14:27:36Z
Keywords: Retreat; Adaptation; Resilience; Sea Level Rise; GIS